Pengaruh Pelatihan Dan Motivasi Terhadap Kinerja Karyawan UMKM Panglawungan Sektor Kerajinan Anyaman Bambu: (Survei Pada Umkm Panglawungan Sektor Kerajinan Anyaman Bambu) - Dimas Achmad Fauzan (CV. ULIL ALBAB CORP, 2022)
: This purpose of this study to determine the effect of traaining and motivation on employee performance at UMKM Panglawung Sektor Kerajinan Anyaman Bambu (Survey at UMKM Panglawungan Sektor Kerajinan Anyaman Bambu). The method used is a quantitative method with a research sample of 112 respondents who are an employee at UMKM Panglawungan Sektor Kerajinan Anyaman Bambu. The data is used primary data and secondary data. The analitytical tool in this research is multiple regression using by SPSS version 25. The result showed that simultaneously training and motivation has a significant influence on employee performance. Partially training has a significant influence on employee performance. Partially motivation has a significant on employee performance.